Journey to Goliad - Cuate, Melodie A. (Book collections on Project MUSE., 2009)
When Mr. Barrington takes his students to an archaeological dig at Presidio La Bahia, Hannah, Jackie, and Nick travel back to 1836 when the Presidio was known as Fort Defiance, just weeks before the Texan and Mexican armies clash at the Battle of Coleto.